THE EFFECT OF ETNOPEDAGOGY APPROACH AND SOCIAL SKILLS ON LEARNING OUTCOMES OF SOCIAL SCIENCE STUDENTS IN CLASS V OF STATE ELEMENTARY SCHOOL 167643, TEBING TINGGI CITY - Selwen Naden; Samsidar Tanjung; Siman Siman (SENSEI RESEARCH CENTER, 2021)
The purpose of this research for: (1 Mknowing the differences in social science learning outcomes of students who are taught with an ethnopedagogical approach compared to students who are taught with a direct approach; (2) Knowing the difference in learning outcomes of students who have high social skills compared to students who have low social skills; (3) Knowing the interaction between learning approaches and social skills in influencing students social science learning outcomes. The sample in this study was the fifth grade students of the State Elementary School 167643 Tebing Tinggi City for the 2020/2021 academic year as many as 54 students. Collecting data in this study through social skills questionnaires and social science learning outcomes tests. Hypothesis testing is done by using the Two Way Anova test. The results showed that: (1) The social science learning outcomes of students who were taught using the ethnopedagogical approach were higher than those with the direct approach (Fcount = 7.750 and sig. 0.008 <0.05); (2) The social science learning outcomes of students who have high social skills are higher than those of students who have low social skills (Fcount = 5.097 and sig. 0.028 <0.05); and (3) There is an interaction between the learning approach and social skills in influencing students social science learning outcomes (Fcount = 6.268 and sig. 0.016 <0.05).